Emotion word type should be incorporated in affective neurolinguistics: a commentary on Hinojosa, Moreno and Ferré (2019). Issue 7 (3rd September 2020) - Wu, Chenggang; Zhang, Juan
ABSTRACT: In this brief commentary, we propose the emotion word type that has not been elucidated in the review (Hinojosa, J. A., Moreno, E. M., & Ferré, P. (2019). Affective neurolinguistics: Towards a framework for reconciling language and emotion. Language, Cognition and Neuroscience . Advance online publication. doi:10.1080/23273798.2019.1620957) should be incorporated in affective neurolinguistics. Emotion words, as a category against neutral words, are a mixture of two sub types: emotion-label words (e.g. joy, sorrow) and emotion-laden words (e.g. reward, snake). Differences between the two kinds of words have been confirmed in numerous studies. The discrepancy of the two types of words has the potential of contributing to the definition and categorisation of emotion words and provides a new interface for affective neurolinguistics, affective neuroscience, and cognitive neuroscience.